Compensation fund as a tool for sustainable development of the Arctic indigenous communities - Novoselov, Andrey; Potravny, Ivan; Novoselova, Irina; Gassiy, Violetta (Polar Science, 2021)
The paper examines the approaches to the formation of compensation funds for the indigenous peoples during Arctic industrial development. The key challenge is the technical problem-solving of reconciling the rights of indigenous peoples and the interests of the mining company. The compensation fund allows harmonizing the interests of stakeholders. In 2020, Russia adopted the Arctic Development Strategy that supposes the implementation of investment projects, social and economic development, improving the quality of life of the local population as well as a creation of stable financial basis for traditional lands. The case-study of Yakutia is analyzed in the paper. The authors consider the possibilities to develop compensation funds on the base of economic, social and cultural impact assessment to fulfill them by the costs of extractive companies. The proposed mechanisms help generate additional income and accumulate financial capital for future generations. The mathematical tools and methods allow problem-solving on assessment of the priority compensation projects, the development of procedure for their implementation and the investment approach for the indigenous participation in the projects of extractive companies. The data for calculations was collected by the authors during field work on the impact assessment of mining projects in the Arctic Yakutia in 2016–2020. journal article